Komunikasi Interpersonal dan Motivasi Terhadap Kinerja Karyawan - Fitria Nurul Hajijah; Ivan Gumilar Sambas Putra (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This study analyzed the effect of interpersonal communication and motivation on team member performance. The sample of this research is PT Soka Cipta Niaga Bandung. The research method used is descriptive and verification methods. Data was collected using a questionnaire in the form of Google Forms. The sample in this study was 62 respondents. Data processing was carried out using multiple linear regression analysis, model fit test, and hypothesis testing with the T-test, and data processing assisted with SPSS software tools version 27.0. The findings of this study prove and provide results that Interpersonal Communication has a positive and significant effect on team member performance, and motivation has no positive or significant impact on team member performance. In conclusion, there is an influence of interpersonal communication and motivation on team member performance Keywords: Interpersonal Communication, Employee Performance, Motivation